2019
DOI: 10.3389/fnins.2019.00702
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic Modulation of Orexin Neurons Reverses Changes in Anxiety and Locomotor Activity in the A53T Mouse Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease. PD symptomology is recognized as heterogeneous and in addition to motor function decline includes cognitive, mood, sleep, and metabolic disorders. Previous studies showed early reductions in anxiety and locomotion in the A53T mice model of PD. Since inflammation and astrogliosis are an integral part of PD pathology and impair proper neuronal function, we were keen to investigate if behavioral changes in A53T mice are accompanied by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 83 publications
(119 reference statements)
2
16
0
Order By: Relevance
“…Hyperactivity was previously observed in this animal model [ 53 ], but this is not the sole factor contributing to reduced fat mass in the A53T mice. Moreover, in our recent, less extensive study, we observed increased exploratory locomotion in A53T mice as well [ 54 ]. In a similar transgenic mouse model of PD (A53T expression driven by Thy1 promoter), Rothman et al [ 55 ] showed that metabolic perturbations are present.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Hyperactivity was previously observed in this animal model [ 53 ], but this is not the sole factor contributing to reduced fat mass in the A53T mice. Moreover, in our recent, less extensive study, we observed increased exploratory locomotion in A53T mice as well [ 54 ]. In a similar transgenic mouse model of PD (A53T expression driven by Thy1 promoter), Rothman et al [ 55 ] showed that metabolic perturbations are present.…”
Section: Discussionmentioning
confidence: 86%
“…After transfection, we subjected them to an experimental procedure assessing exploratory locomotion, SPA, and EE. In our earlier study, we showed that chemogenetic inhibition of orexin neurons ameliorated elevated exploratory locomotion in 5-month-old mice [ 54 ]. As hypothesized, we showed that chemogenetic inhibition of orexin neurons ameliorated exploratory locomotion, SPA, and EE impairments present in 7-month-old A53T mice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous postmortem studies revealed the existence of LBs in the hypothalamus of PD patients (40). A recent study also identified a-synuclein accumulation in orexinergic neurons in an A53T mouse model of PD (41). Lessig et al (9) demonstrated a significant negative correlation (r = −0.447, P < 0.05) between orexin-A levels and a-synuclein aggregation in DLB patients, consistent with previous PD studies showing a-synuclein accumulation in hypocretin-containing neurons in the hypothalamus (6,42).…”
Section: Cerebrospinal Fluid Orexin-a Levels In Lewy Body Disease and Alzheimer's Disease Patientsmentioning
confidence: 84%
“…While the literature is unanimous that chronic 1mg/kg CNO does not grossly change mouse behavior in non-DREADDexpressing mice, the literature is mixed on the effects of acute CNO given to non-DREADDexpressing rodents. Several studies report acute CNO or C21 does not change behavior in non-DREADD-expressing rodents (1mg/kg [our data, 22] or 3 mg/kg [4,21] CNO, or 3.5mg/kg C21 [4]). Of studies that do report a change in behavior in non-DREADD-expressing rodents after acute CNO, two saw behavioral effects in rats with acute 1mg/kg CNO [7,26] and two in mice and rats with higher CNO doses than the present work [4,6].…”
Section: Discussionmentioning
confidence: 87%
“…However, other data do not support a behavioral or physiological effect of back-metabolized clozapine [6,21,22]; for example, in non-DREADD expressing animals, CNO (<5mg/kg) does not substitute for clozapine. To understand this apparent discrepancy -1mg/kg acute CNO decreases locomotion, but <5mg/kg CNO is not discriminated -it is important to directly assess the influence of CNO on fundamental behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%